Dilemma theory: towards a conceptual framework for intercultural management teams - Besso-Cowan, Jonathan Michael (Cranfield University, 2003)
The primary contribution of this thesis is to extend the application of dilemma theory from the study of individuals, to the study of what actually happens, at the level of intercultural encounter in small groups of managers. The thesis makes additional conceptual contributions to the domains of culture, small groups and trust. This thesis explores what insights may be gained from applying dilemma theory to intercultural team dynamics. It adopts a phenomenological perspective, specifically drawing on Hampden-Tumer’s dilemma theory and Levinas’ philosophy of ethical hermeneutics. The thesis explores the conceptual derivation of dilemma theory. It explores the concepts of the virtuous circle, spiralling towards resolution (Bateson’s ‘pattern which connects’) and the alternative vicious circle, exhibiting increasing instability until splitting occurs. An alternative derivation of dilemma theory from Halacha (‘The Way’ of Jewish Law) which guides this author, is suggested. The thesis applies primarily qualitative methods of data collection to an intense study of small intercultural group processes over time. Data was obtained from two culturally diverse teams of six people, by hermeneutic analysis of semi-structured interviews, transcripts of audiotaped team discussions and the teams’ collective written descriptions of their progress. Triangulation of these three methods can be considered as a hermeneutic variant of dilemma methodology allowing the patterns of interactions in the teams, arising out of the interactions of values and their resolution or otherwise, to be measured and team process dynamics to be described. The results were supported by the Thomas Kilmann Conflict Mode Instrument, which allows for resolution. The more cohesive group showed a tendency to dilemma resolution and embracing diversity. The other group worried about diversity, ignored the concerns of the most obviously ‘other’ team member, was distressed and almost fragmented, showing a lesser ability to resolve dilemmas and a tendency to splitting. This thesis concludes that there is a general ability to resolve dilemmas in cohesive teams which value diversity and a lesser ability in teams, which suffer from considerable disharmony. If a team is considered as a fractal of a larger society, the contribution may have relevance to all forms of diversity.